Georgia : Staff Report for the 2001 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2001)
Georgia's medium-term economic goals are to reestablish fiscal and external sustainability and reduce poverty. The conduct of monetary policy has remained sound. Fiscal consolidation has been supported by important measures to strengthen public expenditure management and improve fiscal transparency. Measures to combat corruption, restructure the energy sector, and privatize key enterprises must be accelerated in order to underpin faster growth and poverty reduction. Georgia's efforts to restore its solvency will require continued international support, including further concessional lending and external debt rescheduling.